Two new records of deep sea shrimp under the genus Parapontocaris (Crustacea: Decapoda: Crangonidae) from the southwestern coast of India - Kuberan, G.; Chakraborty, Rekha Devi; Purushothaman, P.; Maheswarudu, G. (Zootaxa, 2018)
This paper reports the occurrence of two species of the crangonid genus Parapontocaris Alcock, 1901 in waters off  Kerala from the southwestern coast of India, viz. P. levigata (Chace 1984) and P. bengalensis (Wood-Mason & Alcock 1891). Although P. bengalensis was reported off Bay of Bengal in India, after 121 years this species was now recorded off Kerala, Arabian Sea. Specimens were obtained at a depth of 250–300 m from Kalamuku (9°59'02.91"N /76°14'33.14"E) and Sakthikulangara (8°56'60.78"N /76°32'34.27"E) fish landing centres. Interspecies genetic divergence (COI: 8.8–9.1% & 16S DNA: 2.1–6.2 %) was recorded in the present specimen P. bengalensis and NCBI sequences.